Working the Fields of Image: The Power of Pictures in a Chinese Village - Radaelli, Isabella (Richtmann Publishing, 2012)
The camera is a powerful tool for producing images: in a moment the pictures are fixed, immobile, eternal. They can depict aparticular moment in a particular place, from a single perspective, that of the photographer. But once printed, they can be transmittedfrom one person to another, producing different feelings, thoughts, dispositions, positive or negative reactions and the like amongst thesubjects involved. What if the person taking the pictures were to asks the subjects usually portrayed by the others’ gaze and lens tobecome their own recorders of their family environments? In this paper, I will present the social and ethnographical use of photographydrawing on my own experience in a small agricultural village in the Southwest of China, among a local matrilineal community, the Mosuopeople. I will try to trace the steps of an informal project I have conducted, asking them to portray by themselves their own family andenvironmental context, showing the difficulties they experienced handling a camera and the outcome achieved. I will also show how,during my fieldwork, having a camera and taking pictures helped me to make friends with the families of the village; and how thecirculation and sharing of the printed images produced different and dynamic interactions among the locals.